ISOLATION AND IDENTIFICATION OF POTENTIAL METHYL PARATHION DEGRADING BACTERIA FROM GWALIOR ARABLE SOIL - JYOTI SHARMA; K.C. GUPTA; A.K. GOEL (International Journal of Pharma and Bio Sciences, 2013)
Twenty one bacterial isolates were isolated from methyl parathion treated agricultural soil from in and around the Gwalior city, Madhya Pradesh to study the degradation of Methyl Parathion. Isolation was done by enrichment in Basal mineral medium with 50 mg/L methyl parathion as sole carbon and energy source. No supplement as a carbon and phosphorus source was added in medium. Methyl parathion utilizing capacities of twenty one isolates were studied with variable concentration of methyl parathion, ranging from 50 mg/L to 1600 mg/L in basal mineral medium. Three isolates EMP11c, EMP12a and EMP12b showed the highest degradation i.e. 97%, 96.4% and 99.9% of 1200 mg/L methyl parathion respectively after 48 hrs at 30°C and 7 pH. The degradation of methyl parathion was analysed by GC-MS. These bacterial isolates were identified as Pseudomonas diminuta (EMP11c), Pseudomonas putida (EMP12a) and Pseudomonas aeruginosa (EMP12b), on the basis of biochemical characteristics and 16S rRNA sequence analysis.